Pengelolaan Lingkungan Desa Wisata Edukasi Berbasis Pemberdayaan Masyarakat di RW 03 Cempaka Putih Timur Jakarta Pusat - Syifa Aulia (Peneliti.net, 2023)
Abstract Environmental problems have become a problem that threatens human life as inhabitants of planet earth and everything in it. The community does not fully have awareness of environmental cleanliness. The background is because the community has minimal knowledge and skills in managing the environment and utilizing recyclable waste to produce economic value. In addition to the problem of community quality, the lack of quantity of people who care about environmental management is also a trigger for environmental problems. Therefore an educational tourism village environmental management activity was formed which aims to carry out a community empowerment process in managing the educational tourism village environment while at the same time making changes in terms of environmental conditions to become sustainable. The method used is a description method with a qualitative approach with the intention of collecting, compiling, and analyzing the results of the research discussed. As a result, the community empowerment process in managing the educational tourism village environment can be said to be running according to the plans that have been designed and the environmental conditions are clean and sustainable.